Implementasi Penyerahan Urusan Pemerintahan Kabupaten kepada Pemerintah Desa: (Studi Kasus Kabupaten Luwu Utara) - Amsal (Jurnal Bina Praja, 2009)
In order to bring services closer to the community, in accordance with the conditions and character or characteristics of the local community, several district government affairs must be handed over to the village government, as mandated by Law No. 32 of 2004 concerning Regional Government. This is to reduce the gap and dependence of villages on the district, as well as to improve the implementation of village autonomy in a real and responsible manner. In its implementation as found in the case study in North Luwu Regency, it turns out that the implementation of the transfer of government affairs from the district to the village is still not as expected, because it is still surrounded by various problems, which must be overcome, for the success of village autonomy in improving community welfare.